Beliefs about Islamic advertising: an exploratory study in Malaysia - Shafiq, Ali; Haque, A. K. M. Ahasanul; Abdullah, Kalthom; Jan, Muhammad Tahir (Emerald Publishing Limited, 2017)
Purpose – This paper aims to explore people’s beliefs towards Islamic advertising. Design/methodology/approach – Being exploratory in nature, this paper applies qualitative method of research by adapting thought elicitation technique of data collection. This method rests in the projective techniques of data collection and is also known as “word association technique”. It allows free thinking of respondents that helps in generating rich data which is most required in qualitative studies. Findings – Various beliefs regarding Islamic advertising were extracted and categorized into different dimensions. These dimensions pertained to Islamic advertising’s possibility, nature, characteristics, real-time decisions and potential outcomes. Research limitations/implications – Being an exploratory study, the data are collected from a small sample, hence raising generalization issues. Though, the same opens avenue for future research in that these dimensions should be subject to validation via large sample size. Practical implications – This research will help in developing a scale to measure attitudes towards Islamic advertising, which the researchers can use to find justification for using Islamic advertising. Such application has great implications for businesses, as Islamic advertising concept stands contrary to the contemporary practices. Social implications – With a growing concern for business ethics, this research is an attempt to bring Islamic ethics into advertising practice. This will not only eradicate the ill-effects of contemporary advertising but also provide sound evidence for revising advertising policies. Originality/value – It adds to the developing field of Islamic marketing, by being the first attempt of its kind in paving the way for Islamic advertising.